Integrating Authentic Research Into the Emory-Tibet Science Initiative - Nusslock, Robin; Gerardo, Nicole M.; Mascaro, Jennifer S.; Shreckengost, Jacob; Balgopal, Meena M. (Frontiers in Communication, 2022)
We are at a historic point in which scientists and Tibetan monastics are working together to investigate ancient questions of mind and matter, and to serve the best interests of humanity. To facilitate this collaboration, His Holiness the Dalai Lama supported the development of the Emory University-Tibet Science Initiative (ETSI), which reflects the first major change in the Tibetan monastic curriculum in six centuries. Over the course of a six-year long curriculum, Tibetan monastics living in India have the opportunity to study science with experts in various disciplines. In 2019, ETSI graduated its first cohort of monastic students, and now has entered the ‘sustainability phase’. A goal of the sustainability phase is to broaden the scope of ETSI and begin training monastics through research. The present paper provides an overview of a three-year Research Training Program being developed for the sustainability phase. We first overview a pilot program that informed feasibility and potential structure for a broader Research Training Program at the monasteries and monastic universities in India. Next, we discuss the conceptual framework for the Research Training Program and four learning objectives that we hope to attain. We then discuss the specifics of the course design for the proposed three-year research training curriculum, through which our goal is to transition from a more guided training experience to a less guided experience. Finally, we discuss challenges and opportunities that we expect to encounter in developing and implementing the Program.